Transformasi Ekonomi Digital dan Implikasinya pada Perekonomian Nasional - Ferdinand Tarorogo Wau; Samanoi Halowo Fau; Jurisman Waruwu (Jurnal Ekonomi dan Bisnis Nias Selatan, 2023)
This study aims to determine the transformation of the digital economy and its implications for the national economy. This type of research uses qualitative descriptive analysis and data collection in the form of literature studies. Therefore, it is obtained from several references including articles, books, or other scientific works related to the topic of discussion. Based on research, shows that the Indonesian economy, which used to use a traditional economy, is now transitioning into a modern economy using a trading system using digital technology to strengthen the economy. One example of a business in the digital economy is e-commerce. Indonesia is the highest country with the world in the use of e-commerce in 2021. The existence of a digital economy can have an impact on the Indonesian economy, which can be used as a business opportunity for MSMEs because it can market products on a wider scale, more effectively, and inexpensively. This can have the effect of reducing unemployment, namely by absorbing labour which becomes the strength of the national economy.